Technical writing essentials : introduction to professional communications in the technical fields - Last, Suzan; Neveu, Candice; Smith, Monika; University of Victoria (B.C.); BC Open Textbook Project; BCcampus (University of Victoria, 2019)
"This open textbook is designed to introduce readers to the basics of professional communications in technical fields: audience and task analysis in workplace contexts, clear and concise communications style, effective document design, teamwork and collaboration, and fundamental research skills"--BC Campus website.
What is technical communication -- Professional style -- Document sign -- Teamwork and communication -- Research methods -- Citing and documenting sources in IEEE style -- Common document types -- Oral and visual presentations -- Appendices. Academic writing basics.
This work is licensed under the Creative Commons Attribution-NonCommercial-ShareAlike License.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Description based on online version; Title from PDF (viewed on September 4, 2019).
Keywords: Technical writing -- Textbooks; Communication of technical information -- Textbooks; Business writing -- Textbooks; Communication -- Textbooks; Electronic books